2022
DOI: 10.1190/geo2022-0196.1
|View full text |Cite
|
Sign up to set email alerts
|

MEANet: Magnitude estimation via physics-based features time series, an attention mechanism, and neural networks

Abstract: The traditional magnitude estimation method, which establishes a linear relationship between a single warning parameter and the magnitude, exhibits considerable scatter and underestimation. In addition, the extraction of features from raw waveforms by a deep learning network is a black box. To provide a more robust magnitude estimation and to construct a deep learning network with an interpretable input, in light of deep learning and earthquake rupture physics, we have established a magnitude estimation networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In addition, they may implicitly pay close attention to features such as event location or timing while ignoring truly salient components of the seismic waveform, which may lead to a decrease in accuracy in practical applications. To overcome this problem, recent studies have shown that combining deep learning with physics parameter-based features can improve the performance of the deep learning model (Kong et al, 2022;Song et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they may implicitly pay close attention to features such as event location or timing while ignoring truly salient components of the seismic waveform, which may lead to a decrease in accuracy in practical applications. To overcome this problem, recent studies have shown that combining deep learning with physics parameter-based features can improve the performance of the deep learning model (Kong et al, 2022;Song et al, 2023).…”
Section: Introductionmentioning
confidence: 99%